Televison Viewing Behaviour of Rural Women (Indian Journal of Extension Education, 2011)
The role of mass media as an instrument for social,cultural and economic changes is such more vital today than over before. This is on account of the revolution in information sciences all over the world. Mass media can provide attention on different development programmes,mobilize people and give them opportunity to expresstheir reactions.They can inform people about needs and problems, innovations and results. Television plays an important role in non-formal education and deals with important issues relating to social and economic progress of rural people in the world. Television is an electronic magic carpet that transports millions of people each day to the very distant places. It is having significant influence on people’s behaviour, relations, values, interests and attitudes etc. television has been typing to meet viewing needs to some specific sections of society such as women, children, youth and students. Speical efforts have been made to telecast programme for women. Various programmes on television are essential for improving self image and self confidence of the rural women.